2020
DOI: 10.3390/polym12071521
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Inhibit IMQ-Induced Psoriasis-Like Inflammation by Inhibiting ICAM-1 Production in Mice

Abstract: Lycopene is the most abundant carotenoid in tomatoes, which has been identified to have the properties of anti-inflammation in addition to the capability to inhibit the expression of adhesion molecules. Intercellular adhesion molecules play a critical role in the pathogenesis of psoriasis. Here, we report that the topical use of a lycopene decreased imiquimod (IMQ)-induced psoriasis-like inflammatory responses, the progress of which was based on adhesion molecules. In vitro analysis showed that lycopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In a previous study, lycopene suppresses the imiquimod (IMQ)-induced psoriasis-like inflammation in keratinocyte, a type of epidermis by inhibiting monocyte adhesion in a mice model. 174 The adhesion molecules include intercellular adhesion molecules (ICAMs) and vascular cell adhesion molecule-1 (VCAM-1), which are significant in inflammatory response. 174 Atopy is associated with an allergic reaction that produces an exaggerated immune response such as eczema, asthma, and allergic rhinitis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, lycopene suppresses the imiquimod (IMQ)-induced psoriasis-like inflammation in keratinocyte, a type of epidermis by inhibiting monocyte adhesion in a mice model. 174 The adhesion molecules include intercellular adhesion molecules (ICAMs) and vascular cell adhesion molecule-1 (VCAM-1), which are significant in inflammatory response. 174 Atopy is associated with an allergic reaction that produces an exaggerated immune response such as eczema, asthma, and allergic rhinitis.…”
Section: Methodsmentioning
confidence: 99%
“… 174 The adhesion molecules include intercellular adhesion molecules (ICAMs) and vascular cell adhesion molecule-1 (VCAM-1), which are significant in inflammatory response. 174 Atopy is associated with an allergic reaction that produces an exaggerated immune response such as eczema, asthma, and allergic rhinitis. Lycopene is useful against atopy occurring in the skin, lungs, and immune-competent cells.…”
Section: Methodsmentioning
confidence: 99%
“…Adhesion molecules play an important role in the migration of T lymphocytes to lesion sites in psoriasis [ 49 ]. In the pathogenesis of psoriasis (especially in its erythrodermic form), the increase in blood vessels and overexpression of ICAM-1 play an important role [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have suggested promising anti-inflammatory, antiangiogenic, anti-invasive, and antimetastatic effects of lycopene [ 146 ]. In in vitro and in vivo (in mice) studies, Shih et al [ 147 ] found that lycopene inhibited IMQ-induced psoriasis-like inflammation in keratinocytes. The researchers conducted the topical treatment with a dose of 0.12 mg/mL lycopene for 7 days and the oral treatment with a dose of 0.12 mg/kg for 42 days.…”
Section: Substances Of Natural Origin—plants and Phytochemicals With ...mentioning
confidence: 99%